Ferromagnetic and multiferroic interfaces in granular perovskite composite xLa0.5Sr0.5CoO3-(1-x)BiFeO3 - Lohr, Javier Hernán (2016)
of ferromagnetic La0.5Sr0.5CoO3 (LSCO) and multiferroic BiFeO3 (BFO) were synthesized by spray pyrolysis method. Different compositions of multiferroic xLSCO-(1-x)BFO composites were synthesized at 800 °C for 2 h. Scanning electron microscopy and energy dispersive spectroscopy elemental mapping were performed to study the morphology of composites. Ferri/ferromagnetic responses above TC (LSCO) are observed, which are associated with the interfaces LSCO/BFO. This interface presents a different behavior compared to the original perovskites, and the magnitude of the magnetization depends on x. Electrical DC conductivity as a function of temperature for LSCO nanopowder (x = 1) presents a different behavior than that reported in bulk material. For x = 1 and 0.9, the model by Glazman and Matveev [Zh. Eksp. Teor. Fiz. 94, 332 (1988)] is proposed to describe the electrical conductivity. On the other hand, x = 0, 0.1, and 0.5 present a variable range hopping behavior. Complex impedance spectroscopy as a function of frequency indicates a pure resistive behavior for x ≥ 0.5 compositions, while a complex resistive-capacitive behavior is observed for low x values (0, 0.1). In these samples, low values of magnetoelectric coupling were measured with an AC lock-in technique.